Shifting the mindset : socially just leadership education - Guthrie, Kathy L.; Chunoo, Vivechkanand S. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Calling others in to lead for social justice has never been more important. In a world plagued by multiple and overlapping pandemics and other crises, the cost of leadership failures is constantly rising. Leadership education is responding to these challenges by centering cultural relevance, critical pedagogies, and important issues of identity, capacity, and efficacy in the preparation of emerging learners. Meeting the global demand for social justice requires thoughtful, innovative, and engaged praxes by all leadership educators. Alongside a cadre of diverse authors, we intend to shift the mindset of leadership education toward forward-thinking and holistic solutions, empowering our students to build a fairer and more equitable world for themselves and others. Shifting the Mindset: Socially Just Leadership Education widens and deepens the discourse begun in Changing the Narrative: Socially Just Leadership Education. Our contributors' ideas occur into two parts: the first examines student social identities otherwise underrepresented in existing leadership education literature. The second portion illuminates key factors of leadership learning contexts frequently un- or underattended in both leadership education and social justice education. Every chapter includes critical considerations and practical guidance for educators striving to meet the leadership demands of an increasingly unjust world. Taken together, these thinking, planning, and acting tools augment the potential of educators who are preparing leaders under uncertain conditions. We envision this book as an essential element of the leadership learning toolkit of socially just leadership educators at all levels, between contexts, and across varying amounts of education, influence, and experience. You are needed now more than ever before. We, once again, invite you to our ongoing fight for fairness, freedom, and a brighter future for all"-- Provided by publisher.
Keywords: Social justice and education.; Leadership -- Study and teaching (Higher); Leadership -- Social aspects.; Group identity.; Education -- Leadership.; Educational strategies and policy.; elektronické knihy; electronic books